De la parodie à la recréation poétique : la réinvention du récit d’aventure scientifique dans l’œuvre de Hugh Lofting - Anne Struve-Debeaux (Strenae)
Drawing inspiration from the scientific travel stories that abounded in the eighteenth and nineteenth centuries, and more particularly from the works of Jules Verne, Hugh Lofting's "Doctor Dolittle" series nevertheless constantly distanced itself from the model it drew inspiration from—a model it never ceased to reinvent in its own way, through humor and fantasy, and which, in doing so, allowed it to express all the complexity of the interwar years, split between confidence and pessimism, as well as the poetry of a universal individual haunted by nostalgia.